Systems delays in the management of malignant breast disease - Dalwai, Ebrahim (Department of Surgery, 2016)
Centralised multidisciplinary management of breast cancer occurs in KwaZulu-Natal, South Africa and requires a diagnostic and staging pathway at the referring hospital. Delays in this pathway are unknown. This study, conducted at a referring hospital, R K Khan (RKK), quantifies and analyses these delays. A retrospective folder review included all patients with breast cancer diagnosed at RKK from January 2008 to January 2009. Data extraction included demographic data, time to diagnosis and initial staging using a standardised datasheet. Specific care steps were identified, namely delays to initial imaging with mammography, pathology confirmation, staging workup and eventual referral to a centralised breast clinic.